Effects and mechanisms of engineered exosomes pretreated with Scutellaria baicalensis Georgi on osteoporosis - Chengbin Long; Xinhang Li; Yueshen Fan; Yingkun Hu; Wenge He; Ning Hu; Fang He (PLoS ONE, 2025)
Osteoporosis (OP) is a common systemic bone disease characterized by reduced bone mineral density and the degeneration of the microstructure of bone tissue. Current therapeutic strategies for OP confront limitations including suboptimal efficacy and substantial adverse effects. This study investigates the therapeutic potential of exosomes derived from bone marrow mesenchymal stem cells (BMSCs) preconditioned with Scutellaria baicalensis Georgi (SBG) for osteoporosis management. Our findings demonstrate that SBG modulates the composition of BMSC-derived exosomes to potentiate osteogenesis. Furthermore, exosomes isolated from SBG-pretreated BMSCs (designated S-EXOs@BMSC) enhance osteogenic differentiation in MC3T3-E1 pre-osteoblasts, a process mediated by upregulating Semaphorin 3A (Sema3A). The efficacy of S-EXOs@BMSC in promoting bone regeneration was corroborated in a murine model of osteoporosis induced by ovariectomy (OVX). These results improve our understanding of how traditional Chinese medicine contributes to OP treatment and emphasize the potential of exosomes from BMSCs grown in SBG conditions as a novel therapeutic strategy for OP.